Visual Exploration Using Acrylic Paint on Used Fashion Items for Sustainable Use - Vairagya Yogantari, Made; Ketut Acwin Dwijendra, Ngakan (International Journal of Psychosocial Rehabilitation, 2020)
Fast fashion is an industrial trend with the concept of cutting time in both production and distribution and others as well as offering new products to the market as quickly as possible. Changes in trends so rapidly driven by big players in the fashion industry where they instill a dogma in the minds of consumers about the ideal fashionable appearance. The development of technology helps fashion goods advertising on social media become more massive so that the decision to buy by consumers becomes faster. Seeing this phenomenon the authors conducted a trial that was applied to the color theory courses of study programs at the Fashion Design Department at the Sekolah Tinggi Desain Bali (STD Bali), Indonesia which had two objectives. The first is to find out how the visual exploration process uses acrylic paint on used fashion items. Second is to observe the added value of used fashion items so that they can be used sustainably. This creative exploration trial was conducted by referring to the reimagine method on the 5Rs (recycle, reuse, reduce, redesign, reimagine) proposed by Esty and Winston (2009), where the added value given to fashion goods is expected to provide more visual appeal so that the use of fashion items can be sustained.